An efficient synthesis of 2-isoxazolines from α-haloketone oximes and dimethyl sulfonium salts. Issue 4 (24th January 2019) - Zhao, Sen; Wang, Hang; Sun, Shaofa; Guo, Haibing; Chen, Zhiyu; Wang, Jian; Wang, Lu; Liang, Steven; Wang, Gangqiang
Graphical abstract: 2-Isoxazolines were synthesized efficiently at ambient temperature from a formal [4+1] cycloaddition of nitrosoalkenes and sulfur ylides, which were generated in situ from α-haloketone oximes and dimethyl sulfonium salts. This approach provides a new method to synthesize a range of 2-isoxazolines in high yields and high regioselectivity. Highlights: A formal [4+1] cycloaddition of nitrosoalkenes and sulfur ylides. Efficient synthesis of 2-isoxazolines. 2-Isoxazolines can be further converted to other well-functionalized building blocks. Abstract: 2-Isoxazolines were synthesized efficiently from a formal [4+1] cycloaddition of nitrosoalkenes and sulfur ylides, which were generated in situ from α-haloketone oximes and dimethyl sulfonium salts. This approach provides a new method to synthesize a range of 2-isoxazolines in high yields and high regioselectivity.